2020
DOI: 10.1002/cac2.12088
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the genetic variants of base excision repair (BER) pathway genes and neuroblastoma susceptibility in eastern Chinese children

Abstract: is the most common non-central nerve system (CNS) solid tumor in pediatrics [1]. Neuroblastoma accounts for approximately 8% of all pediatric cancers but disproportionally causes a high cancer mortality (15%) in children [2]. Pediatric patients with low-risk neuroblastoma witness a 5-year overall survival rate > 90%, whereas the 5-year overall survival rate in high-risk neuroblastoma pediatric patients is < 40% [3]. Genetic susceptibility to neuroblastoma is a promising area of research and needs to be fully i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
(23 reference statements)
0
36
0
Order By: Relevance
“…Details on participants may be found in previous studies. 16 , 30 There were no significant differences between neuroblastoma patients and healthy controls in age (p = 0.823) and sex (p = 0.610).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Details on participants may be found in previous studies. 16 , 30 There were no significant differences between neuroblastoma patients and healthy controls in age (p = 0.823) and sex (p = 0.610).…”
Section: Resultsmentioning
confidence: 84%
“…A total of 313 neuroblastoma patients and 762 healthy controls from the eastern Chinese population were included in the case-control study. 16 , 30 , 44 All participants were unrelated Chinese Han children. The study was approved by each participating hospital Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…The present and previous results (21) indicate that C282Y HFE impacts neuroblastoma characteristics such as therapy resistance and cell proliferation. Several studies reported that single nucleotide polymorphisms (SNPs) in genes [e.g., ATP binding cassette subfamily C member 1 (ABCC1); caspase 8 (CASP8); ERCC excision repair 1, endonuclease non-catalytic subunit/ERCC excision repair 4, endonuclease non-catalytic subunit (ERCC1/XPF or ERCC1/ERCC4); poly(ADP-ribose) polymerase 1 (PARP1); base excision repair (BER); methyltransferase like 14 (METTL14)] are risk factors for neuroblastoma development and patient survival (40)(41)(42)(43)(44)(45). Our data indicate that the frequency of the C282Y HFE SNP in neuroblastoma patients should also be determined in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about SNPs selection and genotyping have been described previously. 41 , 42 , 43 …”
Section: Methodsmentioning
confidence: 99%